Comparison of Polyaniline Performance as A Nitrate EGFET Sensor Layer with Sonication Temperature - Abdullah, Nor Farhana; Mamat, Robaiah; Alif Muslan, Muhammad Izzat; Abdullah, Wan Fazlida Hanim; Manut, Azrif (International Journal of Integrated Engineering, 2025)
The performance of the nitrate Extended Gate Field Effect Transistor (EGFET) sensor has been compared using polyaniline (PANI) with different sonication temperatures, as presented in this paper. PANI was prepared with two sonication temperatures, 28°C and 38°C then employed as the nitrate sensor layers of the EGFET that fabricated on Zinc Oxide (ZnO) and Indium Titanium oxide (ITO) substrate using dip coating method with 15 seconds dipping times. The sensing electrode (SE) was characterized to observe the performance of the nitrate EGFET sensor by comparing PANI performance with different sonication temperatures when interacting with nitrate ions, resulting in sensitivity and linearity of the sensor toward nitrate concentrations. PANI/ZnO exhibits excellent nitrate detection capabilities when prepared at room temperature of 28°C, with a sensitivity of 58.1 mV/dec and linearity of 0.9956. To assess the long-term response of SE, drift measurements were conducted by tested sensor with a 20-ppm nitrate concentration for durations ranging from 1 to 10 minutes where ZnO/PANI SE at 28°C show response gradually decreased over time, exhibiting a drift rate of 83.4 mV/hour over 10 minutes. Consequently, a sonication temperature of 28°C emerges as the ideal parameter for preparing PANI solutions to yield high-performance nitrate sensors.